Utilização de biofertilizante bovino líquido em cultivo de alface crespa (vc. Vanda): concentrações de doses de biofertilizante em cultivo de alface - Silva, José da Conceição Barbosa (Universidade Federal de São Carlos, 2018)
Lettuce is a vegetable composed of leaves is a most consumed in Brazil and therefore we have looked for alternatives of production that reduce its impact on agroecosystems. The work was conducted in the Gehort experimental area of the Natural Resources and Environmental Protection Department of the Agrarian Sciences Center of the Federal University of São Carlos, located in the city of São Carlos, Brazil, with the objective of evaluating the lettuce production in different doses of bovine liquid biofertilizer. of Araras, state of São Paulo, in a red clayey latosol. The experiment was conducted under field conditions in a randomized block design in a 5x8 factorial scheme, that is, five treatments with eight replications, the plot consisting of 24 plants. Curly lettuce (Vanda cv.) Plants were cultivated in polyethylene trays of 200 cells, inert substrate, transplanted at 22 days after sowing and purchased from a suitable company, producer of vegetable seedlings. The treatments were carried out by application of Biofertilizer via foliar, in solution, in concentrations: 20, 40, 60 and 80% of Biofertilizer and mineral fertilization in a treatment as a control. The agronomic parameters evaluated were: head diameter, fresh mass, number of leaves, stem length, stem diameter, stem weight and dry mass. There was a positive effect of the changes of the plants submitted to the concentrations of Biofertilizer, with emphasis on the concentrations of 40, 60 and 80% that favored the expression of the evaluated agronomic parameters.
The use of biofertilizer in liquid cultivation of looseleaf lettuce (vc. Vanda): concentrations of biofertilizer doses in lettuce cultivation
Keywords: Alface crespa cv. Vanda; Biofertilizante; Parâmetros agronômicos; Agronomic parameters; Biofertilizer; Curly lettuce cv. Vanda; CIENCIAS AGRARIAS::AGRONOMIA